Simulation of Bandwidth Management Using Queue Tree and PCQ Techniques in the IT Service Department of PT Pusri Palembang - Daud Rusdi (Institute of Information Technology and Social Science (IITSS), 2024)
The IT Service Building of PT Pusri Palembang is equipped with adequate internet facilities; however, bandwidth distribution across rooms remains uneven, resulting in the absence of fair bandwidth allocation throughout the network. This leads to user competition and reduced internet performance because upload and download limits are not applied per room. Network instability in terms of upload and download speed affects the smoothness of data transmission; thus, bandwidth management is necessary to address these issues. This study applies the Action Research method, consisting of the stages of Diagnosing, Action Planning, Action Taking, Evaluating, and Specifying Learning to analyze the results for future improvements. In the implementation of bandwidth management, the Per Connection Queue (PCQ) and Queue Tree techniques are applied to regulate data flow based on priority levels. The results of the simulation show that the application of bandwidth management in the IT Service Department network is highly effective in reducing bandwidth-related issues in each room and achieving equal bandwidth distribution.